Challenges and Opportunities for Developing Students' Global Skills through Teaching Materials on International Cooperation in Social Science Learning in Minahasa - Siti Fathimah; Andi Tenri; Yoseph Daniel Ari Santie; Dewilna Helmi; Hutri Rizki Amelia (AL-ISHLAH: Jurnal Pendidikan, 2024)
Global skills are important in preparing students to face the demands of today's global society, which is a major concern in the educational context. This study investigates the implementation of social studies learning in Minahasa Regency, particularly in the theme of international cooperation for the development of students' global skills. Using mixed methods design with analysis techniques by Miles, Huberman, and Saldana (2014) and quantitative data analysis including validation and reliability tests and analysis of student response questionnaires. The findings show that currently, the condition of the global skills of grade IX junior high school students in Minahasa through social studies learning on the theme of international cooperation is in the low 50.5%, medium 34.3% and high 15.2% categories. The actual performance gap in the implementation of social studies learning is still not optimal, and it tends to focus on the subject matter and ignore aspects of global skills development. Teachers are more inclined to the traditional knowledge-oriented approach rather than efforts to improve students' global skills. The implications of these findings include the need for a more holistic social studies curriculum reform, intensive teacher training in learning approaches that support the development of global skills, as well as the provision of additional resources such as case-based teaching materials for global studies.